The role of amine sulfates in hydrothermal uranium chemistry. - Norquist, A; Doran, M; O'Hare, D (2005)
A series of novel uranium sulfates containing organic structure directing cations has been synthesized from amine sulfate precursors under hydrothermal conditions. The amine sulfates act as a soluble source of the protonated amines and sulfate ions at low temperature and provide a reaction pathway in which no amine decomposition is observed. The protonated amines act as both space fillers and hydrogen-bond donors in the three-dimensional structure. The factors governing the formation of the observed hydrogen-bonding networks were probed through the use of bond valence sums, which allow the quantification of residual negative charge and determination of the relative nucleophilicity of each oxide ligand. The hydrogen bonding in these new compounds is dependent upon two factors. First, the oxide ligands with the highest nucleophilicities are preferential acceptors with respect to their less nucleophilic counterparts. Second, geometric constraints that result from the formation of multiple hydrogen bonds from a single ammonium center can dictate the donation to oxides with smaller negative charges. Crystal data for [N4C6H12][SO4]2 x 2H2O, a = 7.2651(2) A, b = 7.3012(2) A, c = 8.3877(3) A, alpha = 90.260(1) degrees, beta = 100.323(1) degrees, gamma = 113.0294(15) degrees, triclinic, P-1 (No. 2), Z = 1; for [N4C6H22][UO2(H2O)(SO4)2]2 x 6H2O, a = 6.7318(1) A, b = 9.2975(1) A, c = 13.1457(3) A, alpha = 72.3395(6) degrees, beta = 89.1401(7) degrees, gamma = 70.0267(12) degrees, triclinic, P-1 (No. 2), Z = 1; for [N4C6H22][UO2(SO4)2)2, a = 9.3771(2) A, b = 12.9523(3) A, c = 18.9065(6) A, orthorhombic, Pbca (No. 61), Z = 4; for [N5C8H28]2[(UO2)5(H2O)5(SO4)10] x H2O, a = 7.76380(5) A, b = 14.16890(5) A, c = 56.46930(5) A, orthorhombic, Pbnm (No. 62), Z = 4.